Ignition and Combustion Characteristics of Al/RDX/NC Nanostructured Microparticles. Issue 13 (3rd October 2021) - Young, Gregory; Wilson, Daniel P.; Kessler, Michael; DeLisio, Jeffery B.; Zachariah, Michael R.
ABSTRACT: Nanostructured microparticles composed of nanoaluminum, 1, 3, 5-trinitrohexahydro-s-triazine (RDX), and nitrocellulose (NC) were produced using electrospray assembly and studied in an experimental investigation of their ignition and combustion characteristics. All particles contained 5% NC by weight, while the nanoaluminum content ranged from 23.75 to 85.5% by weight, with the balance being RDX. T-jump wire ignition and laser ignition experiments were conducted with pressures ranging from 0.101 to 5.17 MPa. The T-jump experiments demonstrated that the aluminum component of the particle at least partially combusted anaerobically with the combustion products of the RDX and NC. This was further verified by laser ignition experiments in an inert environment via emission spectroscopy. Broad band light emission was used during laser ignition experiments to characterize ignition delay in both air and inert environments (nitrogen or argon). Ignition delay was independent of gaseous environment suggesting that particle ignition was driven by the decomposition/combustion process of RDX and NC. Ignition delay decreased with decreasing RDX content at 0.101 MPa and decreased asymptotically with increasing pressure.